The general analysis of conflictology in modern linguistic (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with general analysis of conflictology as related to the different levels of language in modern linguistic. The author analyzed the founding and development of conflict solving scientific research, defining the perspective aspects of Ukrainian lingvokonflictology, as a separate branch of linguistic.
Keywords: conflictology; conflicts of language; lingvokonflictology